2018
DOI: 10.1002/adhm.201800623
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and Bioresponsive Two‐Stage Delivery of Therapeutic miRNA via Polyplex Micelle‐Loaded Injectable Hydrogels for Inhibition of Intervertebral Disc Fibrosis

Abstract: Intervertebral disc degeneration (IDD) is frequently caused by gradual pathological changes inside intervertebral discs (IVDs) and progressive fibrosis. MicroRNA‐29 (miR‐29) family possesses potent fibrosis suppression capability, but their application for treatment of chronic IDD is limited due to lack of suitable local delivery systems. In this report, given various overexpressed matrix metalloproteinases (MMPs) during IDD, injectable MMP‐degradable hydrogels encapsulating MMP‐responsive polyplex micelles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 65 publications
1
57
0
Order By: Relevance
“…Most of the efforts on musculoskeletal tissue repair have been concentrated on bone and cartilage tissues via delivery of pDNA encoding for osteogenic (BMP-2, OSX) or chondrogenic (TGF-β3, SOX9) factors [ 33 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 70 , 83 , 90 ], osteogenic siRNA [ 44 , 49 , 71 , 78 , 81 ], mechanosensitive osteogenic/angiogenic miRNA [ 78 , 80 , 82 , 84 ], and chondrogenic mRNA molecules [ 17 ] using alginate [ 33 , 34 , 35 , 36 , 37 , 38 ], fibrin [ 17 , 49 ], chitosan [ 41 , 42 , 44 ], gelatin [ 82 , 90 ], or PEG-based hydrogels [ 70 , 71 , 78 , 80 , 81 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the efforts on musculoskeletal tissue repair have been concentrated on bone and cartilage tissues via delivery of pDNA encoding for osteogenic (BMP-2, OSX) or chondrogenic (TGF-β3, SOX9) factors [ 33 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 70 , 83 , 90 ], osteogenic siRNA [ 44 , 49 , 71 , 78 , 81 ], mechanosensitive osteogenic/angiogenic miRNA [ 78 , 80 , 82 , 84 ], and chondrogenic mRNA molecules [ 17 ] using alginate [ 33 , 34 , 35 , 36 , 37 , 38 ], fibrin [ 17 , 49 ], chitosan [ 41 , 42 , 44 ], gelatin [ 82 , 90 ], or PEG-based hydrogels [ 70 , 71 , 78 , 80 , 81 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…For in situ formation of polyplex micelle-encapsulated hydrogels, these systems were comprised of cationic block copolymers designed to complex mir-29a mixed with PEG gelation precursors and MMP-cleavable peptide crosslinkers. These GAM resulted in an effective MMP-2 inhibition in IDD tissues inhibiting the fibrosis process and reversing IDD in a rabbit animal model [ 84 ] ( Figure 3 ; Table 2 ).…”
Section: Hydrogel-mediated Gene Delivery In Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Another gene delivery method recently applied for the inter-vertebral disc is the polyplex micelle which forms a corona of hydrophilic segments surrounding the core of water-incompatible segments. 57 Feng et al 58 reported a sustained and bioresponsive 2-stage microRNA (miRNA) delivery system into disc NP cells with injectable MMP-degradable hydrogels encapsulating MMP-responsive polyplex micelles. In this study, miR-NA-29 (miR-29) was focused on.…”
Section: ) Polyplex Micellementioning
confidence: 99%
“…The results of this study support that the increase in miR-31-5p level is consistent with the decrease in SDF-1 protein level through Western blot detection. [54][55][56][57][58][59][60] . It is worth emphasizing that the level of miRNAs may be regulated by the methylation of the promoter region, which may affect certain phenotypes 61,62 .…”
Section: Microarray Detection Of Idd Np Was Executed To Analyze the Dmentioning
confidence: 99%